Microgreens dan senyawa yang terkandung didalamnya: Literatur review - Bashariah, Bashariah; Mbusango, Amin; Ningsi, Ratna; Tola, Kati Syamsudin Kadang (UKInstitute, 2024)
Microgreens are plants that are harvested very young usually when they are a few days to a few weeks old with a size between 3-10 cm or depending on the type of plant. The advantage of microgreens lies in their high nutritional content, both in terms of vitamins, minerals, and bioactive compounds. The method in this paper uses a literature study (literature review) which collects data from various scientific articles selected and analyzed articles that are relevant to the field of study. The reviewed literature sources come from journals, books, and other research reports. The growth, quantity and quality of harvested microgreens are greatly affected by the cultivation process and the plant variety itself. Many studies have found that light, growing media, nutrient availability and temperature, are components that affect the quality and quantity of microgreens. The content of microgreens itself has been studied to be at least 4 to 40 times the nutritional content of similar mature plants. Microgreens have higher concentrations of bioactive compounds, such as vitamins, minerals, antioxidants, when compared to similar mature plants. It can be concluded that the potential of microgreens is very high to become one of the materials for further studies related to agricultural and health disciplines.